find p(0),p(-1),p(2) for the following case : p(x)=(x-1)(x+1)
Answers
Answered by
3
hope this solution helps you
Attachments:
![](https://hi-static.z-dn.net/files/dbb/d77b4280f74f1bc14484b66b8df40241.jpg)
Answered by
3
Given polynomial: p(x) = (x-1)(x+1)
To find:
i) p(0)
ii) p(-1)
iii) p(2)
Solution:
I) p(0) = (0-1)(0+1) = -1
ii) p(-1) = (-1-1)(-1+0) = 0
iii) p(2) = (2-1)(2+1) = 3
Follow me please.
Similar questions
Physics,
5 months ago
Math,
5 months ago
Computer Science,
11 months ago
Social Sciences,
11 months ago
Math,
1 year ago